Halal Lifestyle and Generation Z Interest in Saving at Indonesian Sharia Banks: A Mixed-Methods Approach - Rahmi Syahriza; Fauzi Arif Lubis; Putri Ramadani (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the role of the halal lifestyle in shaping Generation Z’s interest in saving at Bank Syariah Indonesia. Research Method: This study employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected via a questionnaire administered to 132 Generation Z respondents in Medan and analyzed using simple linear regression in SPSS 22. Qualitative data were collected through semi-structured interviews with three employees of Bank Syariah Indonesia. Results and Discussion: The study results indicate that a halal lifestyle has a positive and significant effect on Generation Z’s interest in saving with Bank Syariah Indonesia. However, the adjusted R² of 0.135 indicates that this effect remains relatively limited. Qualitative findings indicate that interest in saving is also related to digital services, product innovation, practical needs, and an understanding of Sharia contracts. Implications: Islamic banking needs to strengthen its services, product innovation, and Islamic financial education in line with the characteristics of Generation Z. Originality: This study employs a mixed-methods approach to examine the relationship between the halal lifestyle and Generation Z’s interest in saving, integrating quantitative and qualitative perspectives.